Síntese totais de lisicamina e da (+-)-apomorfina via química de benzino - Muraca, Ana Carolina de Avelar [UNIFESP] (2016)
The benzyne chemistry have been successfully employed in several approches involving total syntheses of natural products and bioative substances. Thus, due to the considerable importance of 2-(trimethylsilyl)aryl triflates in the current context of benzyne chemistry, as well as due to the pronounced biological activities presented by aporphine alkaloids, we developed the total synthesis of lysicamine, an aporphine alkaloid with antileishmanial activity, and the convergent total syntheses of (+-)-apomorphine, an aporphine prototype that acts as an agonist of dopaminergic receptors, employing strategy which has as key steps [4+2] cycloaddition reactions followed by hydrogen migrations between 1-methylene-1,2,3,4-tetrahydroisoquinolines e 2-(trimethylsilyl)aryl triflates, under relatively mild reaction conditions, using cesium fluoride as base and acetonitrile as solvent. The aporphine alkaloid lysicamine and the aporphine prototype (+-)-apomorphine were both obtained in nine steps with overall yields of 24% and 9%, respectively.